Effects of a valved infant-bottle with ergonomic teat on the coordination of sucking, swallowing, and respiration in late-preterm infants. The Safe Oral Feeding randomized Trial - Cresi, Francesco; Maggiora, Elena; Capitanio, Martina; Bovio, Cecilia; Borla, Federica; Cosimi, Sara; Enrietti, Desirèe; Faggiano, Francesca; Loro, Sara; Rovei, Serena Maria; Runfola, Federica; Scrufari, Mariangela; et al. (Frontiers in Pediatrics, 2024)
Introduction: Breastfeeding naturally enables the coordination of sucking, swallowing, and respiration patterns for safe feeding. When breastfeeding is not possible a feeding device that releases milk in response to intra-oral vacuum could potentially offer improved coordination of sucking, swallowing, and breathing patterns compared to conventional devices.The aim of the study is to evaluate the effect of a valved infant-bottle with an ergonomic teat compared to a standard infant-bottle.Methods: This unblinded randomized controlled trial focused on late preterm infants fed by bottle for at least three meals over the day, admitted to the Neonatal Unit of Sant'Anna Hospital (Turin, Italy). Infants were randomized to be fed with a valved infant-bottle with an ergonomic teat (B-EXP arm) or with a standard infant-bottle (B-STD arm). Monitoring included a simultaneous synchronized recording of sucking, swallowing and respiration. The main outcome was the swallowing/breathing ratio.: Forty infants (20 B-EXP arm; 20 B-STD arm) with a median gestational age of 35.0 weeks (IQR 35.0-36.0 weeks) completed the study. Four infants were censored for the presence of artifacts in the polygraphic traces. The median swallowing/breathing ratio was 1.11 (1.03-1.23) in the B-EXP arm and 1.75 (1.21-2.06) in the B-STD (p=.003). A lower frequency of swallowing events during the inspiratory phase of breathing was observed in B-EXP arm compared with B-STD arm (p=0.013).Discussion: the valved infant-bottle with an ergonomic teat improves the coordination of suckingswallowing-respiration and limits the risk of inhalation reducing the frequency of swallowing during the inspiratory phase.